Analisis Indeks Keterancaman Lahan Sawah Di Kawasan Perkotaan Yogyakarta - Firmansyah, Firmansyah; Raharja, Apriadi Budi; Priyandoko, Zulphiniar; Nirbhaya, Yovie (Universitas Galuh, 2024)
The occupation of paddy fields especially in the sub-urban areas of cities. The Yogyakarta Urban Area (KPY) as a National center activity has its magnet for the surrounding area, the physical development of the city forms the conurbation of the City of Yogyakarta with the surrounding satellite areas which is marked by the development of industrial activities, trade in services, education, and settlements. The conversion of agricultural land is unavoidable, especially in sub-urban areas or administrative area transitions, but by estimating the vulnerable paddy fields it is hoped that it can consider the benefits and impacts produced after the conversion of paddy fields. This study aims to analyze the level of threat of paddy fields in the Yogyakarta urban area. Qualitative descriptive approach methods and spatial analysis techniques are based on village administrative units. Analysis of the vulnerability index of paddy fields using GIS (Geographic Information System) analysis techniques which are divided into a level of vulnerability index and an index of disturbance level. The results of the study identified the distribution of paddy fields which were categorized as having low, medium, and high levels of vulnerability and disturbance levels. Then a typological analysis of the Threat level was produced, a low hazard level of +17.7 ha (0.37%), a medium hazard level of +3,741.3 ha (78.45%), and a high hazard level of +1,009.7 ha (21 .17%), the existence of rice fields that have a moderate to high level of threat tends to be scattered around shopping centers, educational centers, near settlements and around the outer ring road corridors.